O trabalho com a leitura nos anos iniciais do ensino fundamental divulgado no Portal do Professor do MEC - Rosado, Lara Oliveira (2018)
The study analyzes teaching proposals for the reading skill for the initial years of Elementary School published in the Ministry of Education (MEC) Teacher Portal since 2008 – year in which the portal was implemented by the Federal Government, for the National Program of Informatics in Education (Proinfo) in partnership with the Ministry of Science and Technology (MCTIC). The aim of the study was to analyze conceptions of reading underlying the teaching proposals for Reading published in the site, including literacy. Methodologically speaking, the research endeavour followed the documentary research line and, theoretically speaking, it followed the contributions of Mikhail Bakhtin. The corpus is constitued of 124 teaching suggestions available on the Portal that demonstrated the predominance of cognitive, romantic and utilitarian approaches to the teaching of reading in the proposals socialized by MEC. Only one class plan seemed aligned with the discursive perspective. With regards to technology, more than half of the proposals do not make use of any multimedia feature, demonstrating that the teaching proposals are distant from the objectives of the portal regarding the incorporation of information technologies in schools.